2015
DOI: 10.1007/s40817-015-0007-3
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between ADHD and Cognitive Profiles of Children with NF1

Abstract: Despite well-accepted findings of a "downward shift" in intellectual functioning in children with neurofibromatosis type 1 (NF1), research has not examined the contribution of the individual indices in this lower performance on intelligence (IQ) measures. Although 30-50 % of children with NF1 meet criteria for a diagnosis of attention deficit/ hyperactivity disorder (ADHD), research has not established the relation between ADHD and intellectual profiles in these children. To clarify these issues, this study ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
4
11
0
Order By: Relevance
“…Intellectual Pro le. Consistent with previous research [13,17], we found that patients with NF1 ADHD showed the lowest IQ scores of all three groups and di ered signi cantly from patients with NF1 control in all measured areas of intellectual ability (Figure 1). Even though mean scores of all scales of the intelligence test lay within normal limits for the NF1 ADHD group, there seem to exist intellectual challenges in this group, which may not represent a serious disability, but could still crucially in uence long-term adaptive functioning and participation.…”
Section: Data Analysessupporting
confidence: 91%
See 4 more Smart Citations
“…Intellectual Pro le. Consistent with previous research [13,17], we found that patients with NF1 ADHD showed the lowest IQ scores of all three groups and di ered signi cantly from patients with NF1 control in all measured areas of intellectual ability (Figure 1). Even though mean scores of all scales of the intelligence test lay within normal limits for the NF1 ADHD group, there seem to exist intellectual challenges in this group, which may not represent a serious disability, but could still crucially in uence long-term adaptive functioning and participation.…”
Section: Data Analysessupporting
confidence: 91%
“…Similar to patients with ADHD-only [15], patients with NF1 ADHD score significantly lower in intelligence tests than healthy (sibling-) controls [14][15][16] and show lower IQ scores than NF1 patients without ADHD (NF1-only) [4,13,14,17]. Also, specific learning disabilities and academic underachievement are associated with ADHD in children, both with and without NF1 [14,16].…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations